Curcumin Plays Neuroprotection Activity by Modulation of Neurotrophic Factor BDNF, GAP-43 and GFAP in Mice with Traumatic Brain Injury (P06-043-19). (13th June 2019) - Sahin, Nurhan; Kilic, Ertugrul; Ates, Nilay; Balcikanli, Zeynep; Orhan, Cemal; Tuzcu, Mehmet; Sahin, Kazim; Juturu, Vijaya
Abstract: Objectives: Curcumin, extracted from the rhizome Curcuma longa, has been shown to be beneficial for neuroprotection in previous studies. In a recent study, a novel formulation of curcumin resulted in an increased relative absorption by 46 times (CurcuWIN®) of the total curcuminoids over the unformulated standard curcumin form. However, the exact mechanisms by which curcumin demonstrates its neuroprotective effects are not fully understood. The present study aimed to investigate the effects of curcumin supplementation on the expression of brain-derived neurotrophic factor (BDNF), glial fibrillary acidic protein (GFAP), a main component of the glial scar, and growth-associated protein-43 (GAP-43), a signaling molecule in traumatic brain injury (TBI). Methods: Brain injury was induced using a cold trauma model in male mice that were treated with curcumin (50 mg/kg) or vehicle via intraperitoneal administration just after TBI. Mice were divided into two groups: TBI + vehicle group and TBI + curcumin (CurcuWIN) group. Results: The results show that curcumin treatment reduced the infarct volume in the brain. TBI induction increased inflammatory cytokines (IL-1β and IL-6), nuclear factor-κB (NF-κB) and GFAP, and reduced BDNF, GAP-43, neural cell adhesion molecule (ICAM) and nuclear factor erythroid 2-related factor 2 (Nrf2) levels in the brain. Interestingly, curcumin decreased the levels of NF-κB, IL-1β, IL-6, and GFAP, and increased BDNF, GAP-43, ICAM and Nrf2 levels in the brain. Conclusions: In conclusion, these results showed that curcumin could increase the levels of BDNF, GAP-43, ICAM, and Nrf2 and attenuate brain injury in the model of TBI. Funding Sources: This study was supported by OmniActive Health Technologies Inc. (NJ, USA). This work was also supported in part by the Turkish Academy of Sciences. Supporting Tables, Images and/or Graphs: